A Stylistic Analysis of Mohsin’s The Diary of a Social Butterfly - Zahid, Eman; Khalid, Tayyaba (Journal of Development and Social Sciences, 2025)
This research examines Moni Mohsin’s The Diary of a Social Butterfly through a stylistic lens while discussing how the novel uses satire to depict an upper-class Pakistani woman who interacts with Pakistani society through social events and modern cultural transformations making it an appealing research object for language study. The research focuses on the lexical and syntactic features of the novel based on Leech and Short’s (2007) model. Through the lexical analysis the writer demonstrates how Mohsin’s selects nouns along with adjectives and adverbs as well as verbs to create satirical elements within the novel. Through syntactic analysis this study examines declarative and interrogative and exclamatory sentence patterns of the text to understand their role in creating the protagonist voice and narrative style. Through his linguistic excellence Mohsin shows ability to create a socially influential text with aesthetic value. This research can be extended by analyzing phonetic and graphical components of text and also with comparisons of South Asian satirical literature.